Struggle for a Home: A Reading of the Male in Kamila Shamsie’s Home Fire - Jerusha Praveena S (ILN Journal: Indian Literary Narratives, 2025)
Home Fire represents the life of British Muslims by modelling on the tragedy Antigone. The novel is modernised with characters whose actions correlate to the characters of Antigone. The story begins in the middle, introducing the grown-up Pasha siblings, and progresses to an end with flashbacks in fragmented narratives that reflect their broken lives. The characters bear the weight of dual identities – immigrants and being a minority (Muslims) – which gives them limited decisions, which they consciously uphold to assimilate and belong in a host country. This article specifically looks at the male characters to study the father-son relationship and the image of a male immigrant. The question of belongingness lingers around the male characters – the longing for a home in the host country and in their own home, where they yearn to be accepted by making their fathers proud.